Integration Of Steam With Constructed Network Media To Improve Mathematics Learning For Class VIII Junior High School Students - Dini Sheila Muflikhah (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This research aims to develop manipulative media for geometric nets to support geometry learning in junior high schools using the Borg and Gall model Research and Development (R&D) method. This media is designed to visualize concrete spatial concepts, increase student interaction, and support the achievement of the Independent Curriculum. Validation shows this media is curriculum-appropriate, mathematically accurate, and practical even though it requires increased durability of digital materials and illustrations. Practicality tests show this media is effective in making abstract concepts more concrete, increasing understanding of students with visual and kinesthetic learning styles, and motivating active involvement, although auditory students require additional guidance. Large-scale implementation shows that this media increases understanding of concepts, learning motivation, and makes learning more interesting. Recommendations include the use of more durable materials, the integration of digital technology, and teacher training to optimize its use